Brief note about plasma catecholamines kinetics and submaximal exercise in untrained standardbreds - Paolo Baragli; Sara Pacchini; Domenico Gatta; Michele Ducci; Claudio Sighieri (Istituto Superiore di Sanità, 2010)
Four untrained standardbred horses performed a standardized exercise test on the treadmill and an automated blood collection system programmed to obtain blood samples every 15 s was used for blood collection in order to evaluate the kinetics of adrenaline and noradrenaline. The highest average values obtained for adrenaline and noradrenaline were 15.0 ± 3.0 and 15.8 ± 2.8 nmol/l respectively, with exponential accumulation of adrenaline (r = 0.977) and noradrenaline (r = 0.976) during the test. Analysis of the correlation between noradrenaline and adrenaline for each phase of the test shows that correlation coefficient decreases as the intensity of exercise increases (from r = 0.909 to r = 0.788). This suggests that during submaximal exercise, the process for release, distribution and clearance of adrenaline into blood circulation differs from that of noradrenaline.